1994
DOI: 10.2466/pr0.1994.74.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Trauma and the Origins of Paranormal Belief: A Constructive Replication

Abstract: Previous research suggests that, as a group, people who believe in the paranormal tend to have a history of traumatic events in childhood. This relationship has been incorporated into Irwin's 1993 model of the psychological origins and functions of paranormal belief. A constructive replication of the relationship and a test of Irwin's model was undertaken in relation to a specific context, namely, a childhood spent with an alcoholic parent. Compared to 89 control participants, a sample of 32 adults who were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
0
11

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 4 publications
8
59
0
11
Order By: Relevance
“…There is reasonable support for Irwin's PFH with self-reported paranormal experiences and/or beliefs linked to global measures of childhood trauma (e.g., Rogers, Qualter & Phelps, 2007) as well as intrafamilial physical abuse (Irwin, 1992;Lawrence, Edwards, Barraclough & Church, 1995;Perkins & Allen, 2006), sexual abuse (Berkowski & MacDonald, 2014;Ross & Joshi, 1992), emotional abuse (Berkowski & MacDonald, 2014;Rabeyron & Watt, 2010), being raised by alcoholic (Irwin, 1994) or overly-authoritarian (Watt, Watson, & Wilson, 2007) parents and domestic instability (Lawrence et al, 1995).…”
Section: *Highlights (For Review)mentioning
confidence: 99%
“…There is reasonable support for Irwin's PFH with self-reported paranormal experiences and/or beliefs linked to global measures of childhood trauma (e.g., Rogers, Qualter & Phelps, 2007) as well as intrafamilial physical abuse (Irwin, 1992;Lawrence, Edwards, Barraclough & Church, 1995;Perkins & Allen, 2006), sexual abuse (Berkowski & MacDonald, 2014;Ross & Joshi, 1992), emotional abuse (Berkowski & MacDonald, 2014;Rabeyron & Watt, 2010), being raised by alcoholic (Irwin, 1994) or overly-authoritarian (Watt, Watson, & Wilson, 2007) parents and domestic instability (Lawrence et al, 1995).…”
Section: *Highlights (For Review)mentioning
confidence: 99%
“…Albeit the psychological functions of paranormal belief have been extensively documented with respect to cognitive tendency of developing schizophrenia (Genovese, 2005;Goulding, 2005;Hergovich, Schott, & Arendasy, 2008;Williams & Irwin, 1991), reality testing (Irwin, 2004), control over life (Irwin, 2000;Watt, Watson, & Wilson, 2007), and false sense of causation (Wiseman & Watt, 2006), there has not been as much empirical research aimed at uncovering the underlying relationships between paranormal belief and cognitive dissociation. In attempts to account for the positive effects of religion on human survival, McClenon (2005) recently postulated in his ritual healing theory that the mental processes of dissociation provided the missing link for explaining how the beneficial effects of paranormal beliefs came about.…”
Section: Paranormal Beliefmentioning
confidence: 99%
“…Thus, the suspension of reality testing may be integral to a broader cognitive style of the person. Motivational factors, such as a need for a sense of control over life events (Irwin, 2004), may also be important here. Thus, if a paranormal belief provides a sense of reassurance in this respect, reality testing of the belief might be suspended and the belief thereby protected against revision in the face of contrary information (Bader, 1999;Wiseman & Smith, 2002).…”
Section: Reasoning and Information Processing Bias In Delusions And Hmentioning
confidence: 99%
“…In this way, an observed event may become the basis for a paranormal belief by the individual. Irwin (2003Irwin ( , 2004 found that paranormal believers have a pattern of reality testing deficits that is characteristic of the formation of psychotic beliefssome people interpret an anomalous event as paranormal without critical testing of the logical plausibility of this belief. On such a basis, people who endorse paranormal beliefs would therefore be predicted to show some deficit in reality testing.…”
Section: Reasoning and Information Processing Bias In Delusions And Hmentioning
confidence: 99%
See 1 more Smart Citation